Expression, purification, crystallization and preliminary crystallographic analysis of spermidine acetyltransferase from Escherichia coli. Issue 8 (31st July 2013) - Niiyama, Mayumi; Sugiyama, Shigeru; Hirose, Mika; Ishikawa, Sae; Tomitori, Hideyuki; Higashi, Kyohei; Yamashita, Tomoko; Adachi, Hiroaki; Takano, Kazufumi; Murakami, Satoshi; Murata, Michio; Inoue, Tsuyoshi; et al.
<x xml:space="preserve">Abstract</x> The spermidine acetyltransferase (SAT) from Escherichia coli catalyses the transfer of acetyl groups from acetyl‐CoA to spermidine. SAT has been expressed and purified from E. coli. SAT was crystallized by the sitting‐drop vapour‐diffusion method to obtain a more detailed insight into the molecular mechanism. Preliminary X‐ray diffraction studies revealed that the crystals diffracted to 2.5 Å resolution and belonged to the cubic space group P23, with unit‐cell parameters a = b = c = 148.7 Å. They contained four molecules per asymmetric unit.